Crucial role of octahedral untilting R3m/P4mm morphotropic phase boundary in highly piezoelectric perovskite oxide. (1st August 2017) - Yan, Kang; Ren, Shuai; Fang, Minxia; Ren, Xiaobing
Abstract: Large piezoelectricity is usually found at morphotropic phase boundary (MPB), a composition-induced phase boundary between two ferroelectric phases. However, only a small fraction of MPBs (e.g., in PZT and PMN-PT) show large piezoelectricity. It remains a long-standing puzzle why not all MPBs yield large piezoelectricity. Here, by a comparative study of two MPB systems of BaZr0.2 Ti0.8 O3 -PbTiO3 (BZT-PT) and Bi0.5 Na0.5 TiO3 -PbTiO3 (BNT-PT), we find that the symmetry relation between the two ferroelectric phases at MPB plays a crucial role in piezoelectric activity. BZT-PT ceramic, having an R 3 m / P 4 mm MPB, exhibits strong piezoelectricity of d 33  = 500 pC/N, whereas BNT-PT ceramic, having an R 3 c / P 4 mm MPB, exhibits much weaker piezoelectricity of d 33  = 150 pC/N. The sharp difference between the two types of R/T MPBs is shown to arise from a significant difference in free energy barrier associated with oxygen octahedral tilting at MPB. An oxygen octahedral tilting/untilting transition at R 3 c / P 4 mm MPB leads to a high free energy barrier and results in low piezoelectric activity, whereas R 3 m / P 4 mm MPB with octahedral untilting produces large piezoelectricity due to low free energy barrier at such MPB. This feature show quite general in most of present MPBs systems and may become a dependable guideline for designing highly piezoelectric Pb-free materials. Graphical abstract: Comparison of typical phase diagrams between (a) high-performance R 3 m /T MPB with octahedral untilting and (b) low-performance R 3 c /T MPB with octahedral tilting.